Core outcome sets in dermatology: report from the second meeting of the International Cochrane Skin Group Core Outcome Set Initiative - Kottner, Jan; Jacobi, Lena; Hahnel, Elisabeth; Alam, Murad; Beeckman, Dimitri; Busard, Celine; Chalmers, J.R.; Deckert, Stefanie; Eleftheriadou, Viktoria; Furlan, Karina; Horbach, Sophie E.R.; Kirkham, Jamie J.; et al. (Wiley, 2018)
Results of clinical trials are the most important information source for generating external clinical evidence. The use of different outcomes across trials, which investigate similar interventions for similar patient groups, significantly limits the interpretation, comparability and clinical application of trial results. Core outcome sets (COSs) aim to overcome this limitation. A COS is an agreed standardized collection of outcomes that should be measured and reported in all clinical trials for a specific clinical condition. The Core Outcome Set Initiative within the Cochrane Skin Group (CSG-COUSIN) supports the development of core outcomes in dermatology.